Relationships Between Beliefs about Medication, Seizure Control and Adherence to Antiepileptic Drugs Among People with Epilepsy - Verma, Archana; K, Kiran; Kumar, Alok (Archives of Clinical and Medical Case Reports, 2020)
Objectives: To determine the relation between beliefs about medication, seizure control and non adherence to antiepileptic drugs (AEDs) in people with epilepsy (PWE) from rural northern Indian community. Methods: Three hundred and eighty five adult PWE were included in the present cross sectional study. Morisky–Green Test was applied for evaluation of adherence level and their beliefs towards usage of AEDs by utilizing Beliefs about Medicine Questionnaire (BMQ). Results: 58.8 % patients were reported non adherent to treatment on the Morisky Green scale. PWE belonging to lower socio economical class has high concern towards the negative effect of AEDs (r=0.200; p<0.001). Patients with lower adherence expressed strong doubts about the necessity of AEDs (r= -0.356; p< 0.01) and increase concern about the negative consequences of taking AEDs (r= -0.433; p< 0.01) as compared to adherent patients. PWE with increased concern has significantly high seizure recurrence (r=0.397; p<0.0001) while believing in necessity of medicines was associated with fewer seizures recurrence (r= -.156; p= .02). Conclusion: Attitude towards AEDs is closely related with adherence. PWE having high concern and low necessity towards AEDs were more non adherent and had poorly controlled seizures. To improve adherence a full and inclusive evaluation of modifiable factors should be made. Present challenge is to create effective interventions to address patients’ doubts about the need for treatment and concerns about adverse consequences in order to enhance adherence. <gdiv></gdiv>